Enhancing efficiency in academic moderation using the online moderation system in public higher learning institution - Abdul Razak, Hanim; Yusop, Yusmarnita; Azmi, Nur Fatihah; Mohd Zin, Mohd Shahril Izuan; Mohd Saad, Wira Hidayat; Haroon, Hazura; Sulaiman, Siti Fatimah; Abdul Karim, Muhamad Fuad (Human Resource Management Academic Research Society, 2024)
Academic institutions face growing challenges in maintaining high standards in assessment moderation. Traditional manual moderation processes are often time-consuming, inefficient, and environmentally unsustainable. This research aims to study the significant difference in moderation time before and after the implementation of the Online Moderation System (OMS) project at Fakulti Teknologi dan Kejuruteraan Elektronik dan Komputer, Universiti Teknikal Malaysia Melaka. Employing a quantitative approach with a cross-sectional design, the study utilizes convenience sampling involving 67 respondents. Descriptive analysis and paired samples t-test were conducted. The findings indicate a significant difference in moderation time before and after the project implementation, (t (66) = 35.12, p < .05). These results demonstrate the effectiveness and efficiency of the moderation process using OMS. Consequently, the system reduced moderation time, promoting effectiveness, efficiency, and productivity among the lecturers.